1995
DOI: 10.3758/bf03199931
|View full text |Cite
|
Sign up to set email alerts
|

Learned variability

Abstract: Potential contributors to sustained levels of variability in the topography of the rat's barpress were investigated in two experiments. Behavior was classified into discretely defined components, and changes in components and their sequential organization were analyzed. Experiment 1 showed that topographic variability in the rat is modulated by shifts in reinforcement schedules. Variability decreased between either dipper training or extinction and continuous reinforcement (CRF), and increased between CRF and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
65
0
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(73 citation statements)
references
References 42 publications
4
65
0
1
Order By: Relevance
“…Earlier work has shown that variability is maintained in a targeted response dimension (Stokes, 1995a). However, we do not know what happens in other aspects of responding.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…Earlier work has shown that variability is maintained in a targeted response dimension (Stokes, 1995a). However, we do not know what happens in other aspects of responding.…”
mentioning
confidence: 78%
“…One manipulation that affects variability involves placing different topographic contingencies on response form. Rats shaped to barpress under an initially high constraint (right paw only) were more variable than those shaped with a low initial constraint (press any way), even after the constraints were reversed (Stokes, 1995a).…”
mentioning
confidence: 99%
“…The question is important for the many cases in which variability is adaptive, for example, in problem-solving, creativity, skilled motor learning, and development of cognitive strategies (e.g., Manoel & Connolly, 1995;Siegler, 1996). In operant-shaping procedures as well, reinforcement presentations are intermixed with temporary withholding of reinforcements, it being thought that withholding reinforcement induces the variability necessary for shaping (Page & Neuringer, 1985;Stokes, 1995). Thus, short-term extinction is part of the shaping process, but what, in fact, is the result of such extinction?…”
Section: Discussionmentioning
confidence: 99%
“…When reinforcement was then withheld, variability increased, with responses now occurring all along the strip (see also Eckerman & Lanson, 1969). Variability induced by extinction has been observed with many other response dimensions, including response force (Notterman & Mintz, 1965), response number (Mechner, 1958), response topography (Stokes, 1995), and response sequences (Balsam, Paterniti, Zechowy, & Stokes, 2000;Mechner, Hyten, Field, & Madden, 1997), and across species, from bacteria to humans. In summary, the evidence is clear that extinction increases response variability.…”
mentioning
confidence: 99%
“…Diversos experimentos vêm explorando esse contínuo variabilidade/repetição, demonstrando que ambos os padrões podem ser operantes, ou seja, dependentes do reforçamento contingente a eles (Barba & Hunziker, 2002;Hunziker, Saldana & Neuringer, 1996;Machado, 1989;Neuringer, 1991;1992;Stokes, 1995). Além das contingências em vigor, tem sido demonstrado que a aprendizagem da variação/repetição pode também sofrer interferência da história do sujeito, como, por exemplo, a ordem de apresentação das contingências de acoplamento ou de reforçamento da variabilidade (Hunziker, Caramori, Silva & Barba, 1998).…”
Section: H L Hunziker E Colsunclassified